O'Keeffe : Days in a Life. - Merrill, C. S. (University of New Mexico Press, 2014)
"Carol Merrill's tribute to Georgia O'Keeffe is poems in the shape of finely rendered sketches, some of them even paintings. These intimate images convey the delicate and tough shape of O'Keeffe's final years in New Mexico."--Joy Harjo, author of She Had Some Horses